An optimization approach to hybrid stations for hydrogen and electric vehicles - Caliskan, Abuzer; Percin, Hasan Bektas (Pergamon-Elsevier Science Ltd, 2025)
Hydrogen/Electric Vehicle Stations (HEVSs) offer various solutions to accelerate the adoption of both hydrogen and electric vehicles, promoting a global transition to cleaner and more sustainable transportation systems. Despite these advancements, research focusing on integrated stations that simultaneously provide hydrogen fuel and charging options remains limited. This study focuses on developing an HEVS and investigates a multiobjective particle swarm optimization (MOPSO) methodology to optimize the overall operation of the station infrastructure. This approach enhances cost-effective operation and facilitates the seamless integration of wind and solar energy within the proposed station. The cost of energy (COE) metric is used to evaluate the study's performance. The COE value obtained by the proposed method (0.59), being close to the reference value (0.55), demonstrates the method's potential to improve the efficiency and reliability of HEVSs, thereby supporting the long-term sustainability and applicability of hydrogen and electric vehicle adoption.
Keywords: Renewable energy; Electric vehicle; Hydrogen; Optimization; Fuel cell vehicle